A multi-institutional quantitative survey of multi-leaf collimator accuracy using a digital picket fence test with sub-millimetre detection capabilities. - Boonzaier, Willem Petrus Engelbrecht (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.